2020
DOI: 10.1037/aap0000181
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies in East Asians’ perceived actual and ideal phenotypic facial features.

Abstract: The present study tested for the existence of a phenotypic actual-ideal discrepancy in East Asians' appraisals of their own faces, in the direction of idealizing a phenotypically "Whiter" face than they perceived themselves to have. The study was conducted in two phases. In the first phase, East Asian participants residing in the U.S. (N = 104; Mage = 18.73) came into the lab to have their photograph taken. They were sent a link to complete the second phase online. Participants were required to recall either t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…There has been a dearth of research on how phenotypicality influences prejudice and discrimination toward Asian Americans. The few existing studies on this topic have focused on physical attraction toward Asian Americans (e.g., Thai et al, 2020 ; Wilkins et al, 2011 ). The current study builds on this literature by exploring how the appearance of Asian Americans (specifically CP) could evoke negative emotional reactions and support for discrimination, especially within the context of an ongoing pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a dearth of research on how phenotypicality influences prejudice and discrimination toward Asian Americans. The few existing studies on this topic have focused on physical attraction toward Asian Americans (e.g., Thai et al, 2020 ; Wilkins et al, 2011 ). The current study builds on this literature by exploring how the appearance of Asian Americans (specifically CP) could evoke negative emotional reactions and support for discrimination, especially within the context of an ongoing pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there is no psychological literature examining the association between Chinese phenotypicality and COVID-19-associated prejudice and discrimination. However, related research investigating the effect of Asian phenotypicality on racism found that Asian phenotypicality in Asian males is negatively associated with attractiveness in Westerners (Thai et al, 2020;Wilkins et al, 2011). Other research suggests that first-generation Asian females with smaller eyes experience more blatant racism (e.g., called names such as "chink") than later-generation Asian females with smaller eyes (Lee & Thai, 2015, p. 245).…”
Section: Racial Phenotypicality and Its Relation To Prejudice And Dis...mentioning
confidence: 99%
“…Studies have explored cues associated with multiple racial and ethnic groups in the U.S. and beyond (e.g., Corneille, et al., 2004; Strom, et al., 2012; Wilkins et al., 2010) and extended to gender cues (e.g., Ko et al., 2009; Sczesny et al., 2006). Research has expanded to include traditionally underrepresented sample populations in the U.S (e.g., Hagiwara, et al., 2013; Thai, et al., 2020), and children (e.g., Jordan & Hernandez‐Reif, 2009). Finally, investigations have explored domains of impact ranging from implicit associations (Uhlmann, et al., 2002) to death penalty judgments (Eberhardt, et al., 2006).…”
Section: Rethinking Racial Stereotypingmentioning
confidence: 99%
“…Furthermore, it should be noted that for the purpose of this research, only two models were used as a means of ethnically appealing to Asian consumers (See Appendix A). While the results of the study show significant correlation between respondent ethnicity and choice of model ethnicity, observable physical trait differences exist between Asian nationality groups (Leow, 2017;Thai et al, 2020).…”
Section: Model Phenotypementioning
confidence: 60%